Description of a new species of the genus Formicococcus Takahashi 1928 (Hemiptera: Coccomorpha: Pseudococcidae) from China - Liu, Qing; Zheng, Xinyi; Xing, Jichun (Zootaxa, 2026)
A new species of mealybug (Hemiptera: Coccomorpha: Pseudococcidae), Formicococcus guiyangensis Liu & Xing sp. nov. is recorded from Guizhou Province, P. R. China. It was found living in bark crevices on trunks of Broussonetia papyrifera (L.) Vent. (Moraceae), beneath carton shelters built by the ant Liometopum sinense Wheeler, W.M. (Hymenoptera: Formicidae). A description and illustration of the adult female mealybug morphology and identification keys to separate the 36 species of Formicococcus found in the Palaearctic and Oriental regions, and the 20 species of Formicococcus found in the East Asian region, are provided.